Conservation of indigenous plants to support community livelihoods: the MGU – Useful Plants Project. Issue 4 (3rd April 2017) - Ulian, Tiziana; Sacandé, Moctar; Hudson, Alex; Mattana, Efisio
Abstract : Through the MGU – Useful Plants Project (2007–2015) led by the Royal Botanic Gardens Kew, high-quality seed collections and research information have been gathered on useful indigenous plants selected by communities in Botswana, Kenya, Mali, South Africa, and Mexico. Local communities were trained in seed conservation, plant propagation, and planting activities, while revenue generation was promoted directly through the sustainable use of plants and plant products and indirectly through wider environmental and cultural services. The success of this project was determined by its participative approach, involving local communities in plant conservation activities and using plant research to support it. However, the promotion of sustainable use and income generation highlighted issues that confirmed the importance of using a 'holistic approach' to address the objective of poverty reduction and contribute to improved livelihoods in the communities.